2022
DOI: 10.11609/jott.7672.14.2.20648-20653
|View full text |Cite
|
Sign up to set email alerts
|

New records of odonates (Insecta: Odonata), Archibasis oscillans Selys, 1877 and Merogomphus tamaracherriensis Fraser, 1931 from Maharashtra, India

Abstract: Archibasis oscillans Selys, 1877 is reported for the first time from Maharashtra, India; and first record of Merogomphus tamaracherriensis Fraser, 1931, based on photographic evidence taken from Sindhudurg, Maharashtra. We report the range extension of both the species in the northern Western Ghats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Ten out of them resulted in the new records to the state of Maharashtra. Koli & Dalvi (2021), Koli et al (2021), and Dalvi & Koli (2022) reported a total of five Odonata species from Sindhudurg District, all of which are first confirmatory records to the state of Maharashtra. In this paper, we report three new records of odonates from Maharashtra, India, and their distribution maps are provided.…”
Section: Introductionmentioning
confidence: 94%
“…Ten out of them resulted in the new records to the state of Maharashtra. Koli & Dalvi (2021), Koli et al (2021), and Dalvi & Koli (2022) reported a total of five Odonata species from Sindhudurg District, all of which are first confirmatory records to the state of Maharashtra. In this paper, we report three new records of odonates from Maharashtra, India, and their distribution maps are provided.…”
Section: Introductionmentioning
confidence: 94%